2016
DOI: 10.18632/oncoscience.299
|View full text |Cite|
|
Sign up to set email alerts
|

Breast tumor response to ultrasound mediated excitation of microbubbles and radiation therapy in vivo

Abstract: Acoustically stimulated microbubbles have been demonstrated to perturb endothelial cells of the vasculature resulting in biological effects. In the present study, vascular and tumor response to ultrasound-stimulated microbubble and radiation treatment was investigated in vivo to identify effects on the blood vessel endothelium. Mice bearing breast cancer tumors (MDA-MB-231) were exposed to ultrasound after intravenous injection of microbubbles at different concentrations, and radiation at different doses (0, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
56
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 43 publications
9
56
1
Order By: Relevance
“…Treatments involving multiple fractions of combined therapy had more apparent arrest of tumor growth and survival using rabbit death and human-modified endpoints and was the only treatment group to demonstrate a trend in where there was arrested tumor growth after 3 weeks (Fig 4). The surviving fraction from combined treatments was similar in comparison to previous observations in PC-3 and MDA-MB-231 tumor bearing mice after 21 days that received lower fractionated doses [21,42], though our results indicate the twice-weekly USMB exposure alone had less effect. The difference in tumor size compared to the mouse model likely plays a role in the decreased induction of endothelial cell damage caused by the USMB treatment, as the acoustic field was applied uniformly towards the more superficial area of the tumor.…”
Section: Plos Onesupporting
confidence: 87%
“…Treatments involving multiple fractions of combined therapy had more apparent arrest of tumor growth and survival using rabbit death and human-modified endpoints and was the only treatment group to demonstrate a trend in where there was arrested tumor growth after 3 weeks (Fig 4). The surviving fraction from combined treatments was similar in comparison to previous observations in PC-3 and MDA-MB-231 tumor bearing mice after 21 days that received lower fractionated doses [21,42], though our results indicate the twice-weekly USMB exposure alone had less effect. The difference in tumor size compared to the mouse model likely plays a role in the decreased induction of endothelial cell damage caused by the USMB treatment, as the acoustic field was applied uniformly towards the more superficial area of the tumor.…”
Section: Plos Onesupporting
confidence: 87%
“…hours after exposure. A similar synergistic enhancement of radiation therapy was observed in bladder [37] and breast [38] xenograft experiments when USMB treatment was used in combination with radiotherapy. These studies demonstrated the mechanism of action for this synergy to be microbubble-induced ceramide-facilitated endothelial cell death.…”
Section: Plos Onesupporting
confidence: 68%
“…vivo in multiple cell lines [15,28,[36][37][38]. Czarnota et al demonstrated that USMB treatment followed by subsequent radiation exposure (2 Gy or 8 Gy) resulted in a synergistic cell death effect in prostate cancer mouse xenografts.…”
Section: Plos Onementioning
confidence: 99%
“…11 Studies have demonstrated that USMBs are effective radioenhancement agents for a variety of cell types in vivo, such as breast, prostate, leukemia, and sarcoma tumors, 15 with additive-to-synergistic effects seen for combinations of USMBs and XRT. 12,15,16 There is evidence to suggest that USMB-mediated radioenhancement results from an endothelial cell insult in the tumor vasculature. Specifically, microbubble excitation initiates apoptosis, likely by inducing sphingomyelinases on the cell surface and subsequently provoking the ceramide pathway.…”
mentioning
confidence: 99%
“…Preclinical studies have demonstrated antitumor effects both with USMBs alone 14 and combining USMBs with external beam radiotherapy (XRT) to achieve synergistic effects 11 . Studies have demonstrated that USMBs are effective radioenhancement agents for a variety of cell types in vivo, such as breast, prostate, leukemia, and sarcoma tumors, 15 with additive‐to‐synergistic effects seen for combinations of USMBs and XRT 12,15,16 . There is evidence to suggest that USMB‐mediated radioenhancement results from an endothelial cell insult in the tumor vasculature.…”
mentioning
confidence: 99%